The S-Layer Glycoprotein of the Crenarchaeote Sulfolobus acidocaldarius Is Glycosylated at Multiple Sites with Chitobiose-Linked N-Glycans. (9th August 2010) - Peyfoon, Elham; Meyer, Benjamin; Hitchen, Paul G.; Panico, Maria; Morris, Howard R.; Haslam, Stuart M.; Albers, Sonja-Verena; Dell, Anne
Abstract : Glycosylation of the S-layer of the crenarchaea Sulfolobus acidocaldarius has been investigated using glycoproteomic methodologies. The mature protein is predicted to contain 31 N-glycosylation consensus sites with approximately one third being found in the C-terminal domain spanning residuesL 1004 -Q 1395 . Since this domain is rich in Lys and Arg and therefore relatively tractable to glycoproteomic analysis, this study has focused on mapping its N-glycosylation. Our analysis identified nine of the 11 consensus sequence sites, and all were found to be glycosylated. This constitutes a remarkably high glycosylation density in the C-terminal domain averaging one site for each stretch of 30–40 residues. Each of the glycosylation sites observed was shown to be modified with a heterogeneous family of glycans, with the largest having a composition Glc 1 Man 2 GlcNAc 2 plus 6-sulfoquinovose (QuiS), consistent with the tribranched hexasaccharide previously reported in the cytochromeb 558 / 566 of S. acidocaldarius . S. acidocaldarius is the only archaeal species whose N-glycans are known to be linked via the chitobiose core disaccharide that characterises the N-linked glycans of Eukarya .